Age and Ageing During the COVID-19 Pandemic; Challenges to Public Health and to the Health of the Public - A. Mark Clarfield; A. Mark Clarfield; Tzvi Dwolatzky; Tzvi Dwolatzky (Frontiers Media S.A., 2021)
The distribution of the SARS-CoV-2 virus has reached pandemic proportions. While COVID-19 can affect anyone, it is particularly hazardous for those with "co-morbidities." Older age is an especially strong and independent risk factor for hospital and ICU admission, mechanical ventilation and death. Health systems must protect persons at any age while paying particular attention to those with risk factors. However, essential freedoms must be respected and social/psychological needs met for those shielded. The example of the older population in Israel may provide interesting public health lessons. Relatively speaking, Israel is a demographically young country, with only 11.5% of its population 65 years and older as compared with the OECD average of >17%. As well, a lower proportion of older persons is in long-term institutions in Israel than in most other OECD countries. The initiation of a national program to protect older residents of nursing homes and more latterly, a successful vaccine program has resulted in relatively low rates of serious COVID-19 related disease and mortality in Israel. However, the global situation remains unstable and the older population remains at risk. The rollout of efficacious vaccines is in progress but it will probably take years to cover the world's population, especially those living in low- and middle-income countries. Every effort must be made not to leave these poorer countries behind. Marrying the principles of public health (care of the population) with those of geriatric medicine (care of the older individual) offers the best way forward.